Kt/V and its association with nutritional status and quality of life in end-stage renal disease patients: a cross-sectional multivariate study - Agatha, Indry; Sunaka, I. Wayan (International Journal of Research in Medical Sciences, 2025)
Background: Dialysis adequacy assessed by Kt/V is a key predictor of outcomes in end-stage renal disease (ESRD). However, its relationship with nutritional status and health-related quality of life (HRQoL) remains unclear in low-resource, single-center settings. Methods: A cross-sectional study was conducted on 65 ESRD patients receiving maintenance haemodialysis (HD) at Wangaya Hospital. Dialysis adequacy was evaluated using single-pool Kt/V. Nutritional status was assessed using BMI and Malnutrition Inflammation Score (MIS), and HRQoL was measured using KDQOL-36. Bivariate and multivariate logistic regression analyses were performed. Results: A total of 70.8% of patients achieved adequate dialysis (Kt/V ≥1.2). Adequacy was significantly associated with BMI (p=0.024), but not with MIS. Among HRQoL domains, only the physical component summary showed a significant association with dialysis adequacy (p=0.014). Multivariate analysis identified employment status and serum albumin as independent predictors of quality of life and nutritional status. Low TIBC and female gender were associated with impaired mental health and higher malnutrition risk. Conclusion: Kt/V-based dialysis adequacy correlates with improved physical functioning and BMI, though not all HRQoL aspects. Findings may support further multicentre research on adequacy and patient outcomes in resource-limited settings.